2003
DOI: 10.1038/sj.jhh.1001508
|View full text |Cite
|
Sign up to set email alerts
|

Dietary risk markers that contribute to the aetiology of hypertension in black South African children: the THUSA BANA study

Abstract: Although clinical hypertension occurs less frequently in children than in adults, ample evidence supports the concept that the roots of essential hypertension extend back to childhood. Since little is available in the literature on causal dietary factors of hypertension in children, this study hypothesised that certain dietary factors can be identified as risk markers that might contribute to the aetiology of hypertension in black children. Children aged 10-15 years were randomly selected from 30 schools in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 40 publications
0
34
1
Order By: Relevance
“…The prevalence of hypertension in sub-Saharan Africa ranged 0-12.5% for boys and 0-21.5% for girls ( Table 1). The highest prevalence rate recorded was 21.5% 31 for girls and 12.5% for boys, 32 whereas Steyn et al 30 recorded the highest total prevalence rate of 22.3% for both boys and girls in urban South African children. Misra et al 19 recorded the highest (20.0%) prevalence of BP for boys in the Asian region followed by Smith and Rinderknecht 14 in the United Staes (13.2%).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The prevalence of hypertension in sub-Saharan Africa ranged 0-12.5% for boys and 0-21.5% for girls ( Table 1). The highest prevalence rate recorded was 21.5% 31 for girls and 12.5% for boys, 32 whereas Steyn et al 30 recorded the highest total prevalence rate of 22.3% for both boys and girls in urban South African children. Misra et al 19 recorded the highest (20.0%) prevalence of BP for boys in the Asian region followed by Smith and Rinderknecht 14 in the United Staes (13.2%).…”
Section: Discussionmentioning
confidence: 93%
“…In general, the studies cited in this review classified the children as hypertensive based on the the guidelines for hypertension. 12,13,31,32,30,[33][34][35] Frontini et al 24 and Barger and Muldoon 25 classified children as hypertensive based on the 140/90 mm Hg recommendation of the WHO. It is clear from the cutoff point of these two studies together with the study of van der Sande et al 22 who used 160/95 mm Hg that the situation might be worse than it is reported in their respective area.…”
Section: Discussionmentioning
confidence: 99%
“…1 For a few decades, noninvasive finger arterial BP measurement (Finapres/ Portapres) has become an accepted technology, widely used in different areas of research, ranging from basic research, such as autonomic control of cardiovascular function, hypertension, pharmacology and psychophysiology, to use in the operating room, clinical practice, aero-and space research. [2][3][4] It has been shown that the vascular unloading technique of Penáz together with the Physiocal criteria of Wesseling provides reliable, noninvasive and continuous estimates of BP. [5][6][7] However, previous studies 7 have indicated that although the Finapres fulfilled the accuracy requirements for the mean and diastolic mean difference (+1.7 mmHg (s.d.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of hypertension found (29) , others almost similar values (13,30) , while a majority of the studies had disproportionately higher prevalence rates of hypertension (Table 5). (1,12,13,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) The likely reasons for the difference between the prevalence of hypertension in this study and those reported in the literature might be the use of different age groups, differing research methods and definitions of BP, as well as differences in reported prevalence and risk estimates. It is possible too, that geographical location may account for the difference in distribution of BP.…”
Section: Discussionmentioning
confidence: 86%
“…Monyeki et al (32) Tunisia 15-19 5.2 Aounalian-Skhiri et al (33) South Africa 10-15 17.2 Schutte et al (34) New Delhi 14-25 20.0 (boys)…”
Section: Discussionmentioning
confidence: 99%